Traumatic fracture of the medial coronoid process in a dog - Görtz, K.; Van Ryssen, B.; Taeymans, O.; Van Heerden, M.; Gielen, I.; Risselada, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
This case report describes an acute traumatic fracture of the medial coronoid process (MCP) in an immature male Rottweiler. On routine radiographs of the left elbow joint, clear abnormalities could not be detected. The definitive diagnosis was based on craniolaterocaudomedial oblique radiographs and a CT scan. The fragment was removed arthroscopically via a medial approach. Histologically the fragment did not show any signs of degeneration nor demineralisation, as seen in classical fragments of the medial coronoid process. One week after treatment, complete limb function had been regained. Follow-up radiographs after nine month showed a minimal increase of osteoarthrosis.
Keywords: Traumatic MPC; elbow arthroscopy